ANALISIS SWOT PELAPORAN MORTALITAS PASIEN RAWAT INAP SEBAGAI PENDUKUNG MUTU PELAYANAN DI RSU AMINAH KOTA BLITAR - Intan Putri Maharani; Prima Soultoni Akbar; Ahmad Jaelani Rusdi (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2022)
As a reference for seeing the number of patients who died due to certain diseases, mortality reports are an important indicator for measuring the success of development in the health sector. Based on the results of research at Aminah General Hospital in Blitar City, it is known that mortality reporting is carried out using two methods, a manual method for processing reporting data and a computerized method for data acquisition. Data collection is written in the visit report in the medical records unit report. One of the efforts made to resolve this problem is to carry out a SWOT analysis of mortality reporting. The purpose of this research was to analyze the SWOT elements of reporting inpatient mortality as a support for the quality of service at RSU Aminah Blitar. This type of research is qualitative descriptive research using the SWOT approach. The results of the FGD (Focus Group Discussion)  show that the most dominant strategy is the WO (Weakness Opportunity) strategy, namely increasing effective communication with professional care provider and related units to minimize incomplete recording of the cause of patient death and to encourage reporting officers not to provide services at the patient registration when the time for reporting is approaching.